Quantifying in international conflict: the linkage approach - KIBECHE, Abdelkrim (Journal of Human Sciences, 2000)
The evolution of international relations has introduced a development in the subject and in the method itself. For instance, the use of quantitative method could improve the international relations science, especially in the study of international conflict. However, many writers still use the qualitative method. In this debate, the author gives an alternative method in the study of the relations between internal and external conflict behaviour.